An Introduction to Social Sustainability and Interior Architecture - Smith, Dianne; Beeck, Sarah; Lommerse, Marina; Metcalfe, P. (Springer, 2014)
Interior architecture is a field that has much to contribute to the discussion and practice of social sustainability. Its potential is not often made explicit, although there are many sources which discuss the design and usage of interiors in relation to material specification, energy consumption and the like; that is, to the relationship to the broader sustainability debate. In contrast, social sustainability captures the human dimension of the sustainability discourse and gives emphasis to people and communities. It is this focus that resonates with interior architecture. We believe that social sustainability is the ability of a society or an individual’s lifestyle to continue in a way that suits their needs and those of subsequent generations. The values and spiritual aspirations of the people should be complemented in their interior environment, and the processes and activities involved should respect their history, current needs and future potential beliefs and rituals. We identified that there are three key areas thin social sustainability where the discipline can meaningfully contribute: community engagement, social justice and cultural heritage. Each area is critical to understanding the relationship between social sustainability and interior architecture in the twenty-first century.